Securing Healthcare Data Exchange Based on Fog Computing and Blockchain Technologies - Jawad, Muwafaq; A. Yassin, Ali; Ali Abed AL-Asadi, Hamid (Iraqi Journal for Electrical and Electronic Engineering, 2026)
IoHT has several benefits for real-time smart healthcare, but because of its limited processing power, storage capacity,and self-defense capabilities, security issues are growing. Although newer blockchain-based authentication solutionshave strong security features due to their tamper-resistant decentralized architecture, they come with a high resourcecost, requiring a lot of processing power, more storage, and time-consuming authentication procedures. As such, thesedifficulties provide barriers to reaching the ideal levels of scalability and temporal efficiency, which are essential forthe efficient functioning of large-scale, time-sensitive IoHT systems. To solve these challenges, this paper presents anauthentication approach designed especially for IoHT systems. Our work consists four-phase process, which includessetting, registration, login and authentication, and HERs Exchange data. To enhance both efficiency and scalability,the proposed scheme employs a combination of 3-D map dimensions chaotic-based public key cryptosystems, andblockchain-based, fog computing technologies and IPFS. We simulate the proposed work to implement health electronicrecord (HER) by the Ethereum platform and solidity language, the simulation experiments were tested using the JMetertool. Showed that the key generation time for chaotic-based is faster than (ECC)—furthermore, the average latency ≈3.7 ms. A security analysis of the proposed scheme was implemented by the Scyther tool. The formal security analysisdemonstrated that the proposed scheme is secured against potential attacks and supports the scalability of the IoHTsystem.